2014
DOI: 10.1007/s11284-014-1212-8
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical nitrogen properties of forest soils in the Japanese archipelago

Abstract: This data paper provides some biogeochemical nitrogen (N) properties and related chemical properties of forest soils from 39 sites throughout the Japanese archipelago. The data set was collected and analyzed under the GRENE (Green Network of Excellence) environmental information project and the ReSIN (Regional and comparative Soil Incubation study on Nitrogen dynamics in forest ecosystems) project. The sites cover 44°20¢N to 26°50¢N and the climate ranges from cool-temperate zone to subtropical zone. At each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…We used cropland soil (Takahashi et al, 1991), rice paddy soil (Itoh et al, 2013), forest soils (Urakawa et al, 2015) and lake sediment (Abe et al, 2000) as described below. All soil samples were collected in triplicate at 5-10 cm depth from each experimental site, and lake sediment was sampled in triplicate at 10 cm depth from the sediment surface using an Ekman sampler.…”
Section: Diversity Of Nirk and Nirs Genes In Various Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used cropland soil (Takahashi et al, 1991), rice paddy soil (Itoh et al, 2013), forest soils (Urakawa et al, 2015) and lake sediment (Abe et al, 2000) as described below. All soil samples were collected in triplicate at 5-10 cm depth from each experimental site, and lake sediment was sampled in triplicate at 10 cm depth from the sediment surface using an Ekman sampler.…”
Section: Diversity Of Nirk and Nirs Genes In Various Environmentsmentioning
confidence: 99%
“…Various environmental samples from terrestrial habitats were used, including a cropland soil (Andosol) applied with an organic fertilizer , a cropland soil (Gray Lowland Soil, Eutric Fluvisol) applied with an organic or urea fertilizer (Takahashi et al, 1991), paddy soils from flooded and non-flooded seasons (Gray Lowland Soil, Eutric Fluvisol) (Itoh et al, 2013), two natural forest soils (Brown Forest soil and Andosol) (Urakawa et al, 2015), a planted forest soil (Brown Forest soil) (Oda et al, 2009) and a lake sediment (Abe et al, 2000). Environmental DNA was extracted as previously described.…”
Section: Abundance and Distribution Of Nirk And Nirs Genes In Variousmentioning
confidence: 99%
“…Two subsamples (7 g each, equivalent to about 3.5 g of dry soil) from each soil sample were used for the analysis of NH 4 + production or nitrification during 24-h incubation. The detailed procedures have been reported previously (Isobe et al, 2011b,c;Urakawa et al, 2014). The concentrations and N isotope ratios of NH + 4 or NO − 3 in the 2M KCl extracts were determined according to the method of Isobe et al (2011b).…”
Section: Production and Nitrificationmentioning
confidence: 99%
“…The forest floor is covered mainly with Dryopteris crassirhizoma. Further details of the study site are given by Urakawa et al (2015). During the entire study period, the ambient temperature at the measurement site ranged between 14.2 and 29.9 • C. Our previous study reported the annual measurements of biogenic VOC fluxes at the same site, which showed that the fluxes were largest in July and August (Mochizuki et al, 2014).…”
Section: Site Descriptionmentioning
confidence: 99%